The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1037/0022-0663.75.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the reader's schema at different points in time.

Abstract: In two experiments, subjects were instructed to take a distinctive point of view while reading and recalling a story. Perspectives assigned before reading, shortly after reading, and long after reading all had substantial effects on recall. The results were interpreted to mean that the schema brought into play by the perspective instructions selectively enhances encoding when operative during reading and selectively enhances retrieval when operative during attempts at recall. The schema operative during readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 24 publications
5
46
0
Order By: Relevance
“…First, the results of this study as well as from previous studies (e.g., Anderson & Pichert, 1978;Anderson, Pichert, & Shirey, 1983;Pichert & Anderson, 1977) suggest that importance of story elements is more strongly related to recall for some perspectives than for others. For example, Pichert and Anderson (1977) presented subjects with either the House passage used in the present study or another study, termed the Island Story, about two gulls frolicking over a remote island.…”
Section: Implications Of the Present Study And Suggestions For Futuresupporting
confidence: 56%
See 2 more Smart Citations
“…First, the results of this study as well as from previous studies (e.g., Anderson & Pichert, 1978;Anderson, Pichert, & Shirey, 1983;Pichert & Anderson, 1977) suggest that importance of story elements is more strongly related to recall for some perspectives than for others. For example, Pichert and Anderson (1977) presented subjects with either the House passage used in the present study or another study, termed the Island Story, about two gulls frolicking over a remote island.…”
Section: Implications Of the Present Study And Suggestions For Futuresupporting
confidence: 56%
“…This result was not identical to the results of previous studies, but it was in the same general direction. Previous studies (e.g., Anderson & Pichert, 1978;Anderson, Pichert, & Shirey, 1983;Pichert & Anderson, 1977) have all found that importance of story elements is more strongly related to recall for the burglar than for the home buyer perspective. In the present study, subjects were apparently unable to use the home buyer perspective as an effective retrieval mechanism.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Examination of the stories and subjects' rank-ordered familiarity ratings sug-gest that Lentil contains more familiar material, which may engage readers' textual and content schemata (Anderson, Pichert, & Shirey, 1983). The schemata, used in concert with cues from the text, serve as a basis for readers' predictions.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Thus, low prior knowledge for the content domain of a text did not always preclude the use of predictions. Readers appeared to use their textual schemata (Anderson, Pichert, & Shirey, 1983) when specific content domain schemata were lacking or poorly developed. In the following protocol excerpt, it is notable that the reader generated a prediction without any reference to the content domain of the text.…”
Section: A Qualitative Analysis Of Readers' Prediction and Predictionmentioning
confidence: 99%